PENAPISAN LIMBAH PERTANIAN (SABUT KELAPA DAN ARANG SEKAM) DALAM PENINGKATAN KETAHANAN BIBIT PISANG BARANGAN BERMIKORIZA TERHADAP BLOOD DISEASE BACTERIUM DAN FUSARIUM OXYSPORUM F.SP. CUBENSE - Suswati .; Asmah Indrawati; Deddi Prima Putra (Universitas Lampung, 2015)
Agricultural waste screening (coconut fibre and chaff charcoal) in improving the resistance of Mychorrizae Barangan seedling to Blood diseases bacterium and Fusarium oxysporum f. sp. cubense. The application of soil and compost are very general in Barangan banana seedling. However, those media always contaminated by BDB and Foc propagul. This research was intended to examine the influence of planting media composition (soil, coconut fibre and chuff charcoal) in improving the resistance of Mychorrizae Barangan banana seedling to blood diseases bacterium dan Fusarium oxysporum f sp.cubense. Some experiments conducted in wirehouse using a randomized complete block design application of two subtracts for soil substitution included to either coconut fibre (A) or chuff charcoal (B) (v:v) completed by 6 treatments of each: A0 = 100% soil media, A1 = 50% soil + 50% chuff charcoal, A2 = 50% soil + 25% chuff charcoal + 25% sand, A3 = 25% soil + 50% chuff charcoal + 25% sand; A4 = 75% chuff charcoal + 25% sand, A5 = 100% chuff charcoal, B0 = 100% soil, B1 = 50% soil + 50 % chuff charcoal; B2 = 50% soil + 25 % coconut fiber + 25% sand, B3 = 25% soil +50% coconut fiber +25% sand; B4 = 75% coconut fiber + 25% sand, B5 = 100% coconut fiber. The soil generated from banana seedling area of Sempakata village that seriously infected BDB and Foc. The observation variables encompassed percentage of disease attack, density of BDB and Foc. population, period of pathogen incubation and measurement of Barangan seed and AMF colonization resistance development. The results indicated the planting of Mychorrizae Barangan banana seeds applied diminishing soil media as much as 25–100% substituted by chuff charcoal or coconut fiber increased the seed resistance of BDB and Foc.